ASOSIASI DAN SEBARAN JENIS Ceriops decandra (Griff.) Ding Hou SERTA KARAKTER HABITATNYA DI TAMAN NASIONAL BALURAN - , Susy Andriani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
some Baluran National Park mangrove has spread throughout of the coastal beaches. One type of mangrove in Baluran National Park is Ceriops decandra which is a rare type possessed by only a few countries. The preservation and cultivation of C. decandra research should start from the character of C. decandra which includes its distribution patterns and association with other species and habitat characteristic in the field. . This study aims to determine association, type and level of association between C. decandra and other species, knowing the distribution of C. decandra in Baluran National Park, and investigate its habitat quality, as seen from the physical and chemical propersties of soil and water in Baluran National Park. The method used in this study is quadrat method. Measurements were made on plots that were placed on mangrove area with C decandra stand inside. Observation and measurements were made from the river/sea to the land. Determination of the sample points and retrieval of data is done by systematic sampling. . The result showed that at the study site, C decandra found at the level of stakes and poles. At the stakes level, C. decandra had a possitive association with Rhizophora stylosa in a relatively low level, whereas at pole level, it had a possitive association with Ceriops tagal, also in low level. These associations occured by the similar substrate prefered of those species. C. decandra had a uniform distribution pattern at stakes level, while at poles level distributed in a clumped pattern formed by the heterogenity of the habitat. Habitat of C. decandra in the study site had a sandy mud substrate with soil pH 8,29, with humidity, organic matter, nutrient, and CEC in low levels, with the other word it can be said that C. decandra could live in an extreme habitat condition.